Substantiation of influence factors on the value stream in the context of lean enterprise management - Kolos, Irina (My University, 2020)
The object of research is the factors of influence in their interaction and subordination with a focus on the generation/destruction of the value stream for the customer / end user in the context of the lean management of the enterprise. Based on the results of the system and critical analysis, the components of the value stream have been identified and justified: human flow, material flow, cash flow, information flow. The priority of human flow is proved, which provides the transformation of material flow with the subsequent generation of cash flow and at the same time reinforcing changes in all components through the information flow. The author’s systematization of factors of influence on the value stream for the end customer in the context of the lean management of the enterprise is proposed according to the following criteria: in the context of the components of the value stream (human flow, material flow, cash flow, information flow); lean-based target (volume, value, quality, time); by the vector of the influence of an individual factor on the value stream (value-added (generating); do not-value-added (destroy); do required non-value-added). According to the results of the structural-logical analysis, grouping, and the graphical method (Ishikawa diagrams), the subordination and causal relationships between the identified factors of influence on the value stream are clearly presented. At the same time, the structuring of factors influencing the value stream is described using a system of multiple tuples of the full combination (value stream). The dependence of the grouping of factors on the vector of influence on the value stream on sectoral characteristics and targets for the functioning of the enterprise and its business partners is determined. It is also advisable to take into account differences in the ways of creating value and competitive advantages in terms of uniqueness of approaches, the pleasure of customer preferences with an orientation toward strengthening and maintaining business activity. There was further development of the application of individual lean manufacturing methods (VSM, SOP, 5 W, JIT, Heijunka, Visual Management, Kaizen) to justify and view a holistic system of factors of influence on the value stream. The active use of these methods will provide accurate with a high degree of detail and agreed upon a list of factors of influence on the value stream, which in the future will allow management to: improvement of management efficiency; implementation of the rational distribution and use of limited resources; formation of a motivation system focused on the contribution to value creation. Об’єктом дослідження є чинники впливу у їх взаємодії й супідрядності з орієнтацією на генерування/руйнування потоку створення цінності для замовника/кінцевого споживача в контексті ощадливого управління підприємством. За результатами здійснення системного та критичного аналізу виокремлено й обґрунтовано складники потоку створення цінності: людський потік, матеріальний потік, грошовий потік, інформаційний потік. Доведено пріоритетність людського потоку, який забезпечує перетворення матеріального потоку з подальшим генеруванням грошового потоку та одночасним підкріпленням змін усіх складників через інформаційний потік. Запропоновано авторську систематизацію чинників впливу на потік створення цінності для кінцевого замовника в контексті ощадливого управління підприємством за такими ознаками: в розрізі складників потоку створення цінності (людський потік, матеріальний потік, грошовий потік, інформаційний потік); за цільовим базисом ощадливості (обсяг, цінність, якість, час); за вектором впливу окремого чинника на потік створення цінності (додають/генерують цінність для споживача; не створюють/руйнують цінність для споживача; не додають цінності для споживача і є невід’ємними). За результатами структурно-логічного аналізу, групування та графічного методу (діаграми Ісікави) наочно представлено супідрядність й причинно-наслідкові взаємозв’язки між виокремленими чинниками впливу на потік створення цінності. Разом з тим, структуризацію чинників впливу на потік створення цінності описано з використанням системи множини кортежів повної комбінації (потік створення цінності). Визначено залежність групування чинників за вектором впливу на потік створення цінності від секторальних особливостей та цільових орієнтирів функціонування підприємства та його бізнес-партнерів. Також доцільно враховувати відмінності у способах створення цінностей та конкурентні переваги щодо унікальності підходів задоволення вподобань замовників з орієнтацією на посилення й підтримування бізнес активності. Дістало подальшого розвитку застосування окремих методів ощадливого виробництва (VSM, SOP, 5 W, JIT, Heijunka, Visual Management, Kaizen) для обґрунтування та перегляду цілісної системи чинників впливу на потік створення цінності. Активне використання зазначених методів забезпечить точний з вищим ступенем деталізації та погоджений перелік чинників впливу на потік створення цінності, що в перспективі надасть керівництву можливість: покращення ефективності управління; здійснення раціонального розподілу й використання обмежених ресурсів; формування системи мотивації, орієнтованої на внесок у створення цінності.
Keywords: ощадливе управління; lean management; людський потік; потік створення цінності; матеріальний потік; грошовий потік; інформаційний потік; value stream; human flow; material flow; cash flow; information flow; кафедра обліку і аудиту